Anatomie Et Histologie De L’hépatopancréas Chez La Femelle Du Poisson, Chloroscombrus Chrysurusde Linnaeus, 1766 (Carangidae) En Côte d’Ivoire - Miessan, Jean-Jacques; D’almeida, Marie-Anne; Kouassi, Komenan Daouda; Yao, Sylvain; N’douba, Valentin; Gnahoue, Goueh (European Scientific Journal, ESJ, 2018)
Chloroscombrus chrysurus is a pelagic fish species that belongs to the Carangidae family. It has a fairly high level of exploitation in Côte d’Ivoire. This paper focuses on the study of the maturity scale, the differentiation, and the histology of hepatopancreas. The methodological approach consisted of a macroscopic description of the hepatopancreas according to the six stages of sexual maturity. The microscopic study consisted of fixing the hepatopancreas, dehydrating them, impregnating them, including them, and making the sections that will be stained for optical microscopic observation. Macroscopic analysis has established six stages of sexual maturity in the species during which the growth and differentiation of hepatopancreas occur. From the juvenile to the adult stage, the size and color of the hepatopancreas vary. On the other hand, its aspect and shape remain unchanged. The hepatopancreas consists of two unequal lobes. The left hepatic lobe is always more developed than the right. On the microscopical level, among the female gender, the hepatopancreas is a mixed organ which constituted the hepatic parenchyme and pancreas. The pancreas differs in the hepatic parenchyma which is composed mainly of polygonal hepatocytes and blood vessels. The hepatocytes are arranged in sinusoidal cords around the capillaries. The pancreas is composed of islets of Langerhans (endocrine pancreas) and serous acini Pancreatic (exocrine pancreas). Both structures progressively invade the hepatic parenchyma. The hepatopancreas is an essential organ in the physiology of fish.